Impact of COVID-19 on liver transplant recipients–A systematic review and meta-analysis - Anand V. Kulkarni; Harsh Vardhan Tevethia; Madhumita Premkumar; Juan Pablo Arab; Roberto Candia; Karan Kumar; Pramod Kumar; Mithun Sharma; Padaki Nagaraja Rao; Duvvuru Nageshwar Reddy (EClinicalMedicine, 2021)
Background: Immunosuppression and comorbidities increase the risk of severe coronavirus disease-2019 (COVID-19) in solid organ transplant (SOT) recipients. The outcomes of COVID-19 in liver transplant (LT) recipients remain unclear. We aimed to analyse the outcomes of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in LT recipients. Methods: The electronic databases were searched for articles published from 1 December 2019 to 20 May 2021 with MeSH terms COVID-19, SARS-CoV-2, and liver transplantation. Studies reporting outcomes in more than 10 LT recipients were included for analysis. LT vs non-LT patients with COVID-19 infection were compared for all-cause mortality, which was the primary outcome studied. We also evaluated the relation between the timing of COVID-19 infection post-LT (< one year vs > one year) and mortality. Findings: Eighteen articles reporting 1,522 COVID-19 infected LT recipients were included for the systematic review. The mean age (standard deviation [SD]) was 60·38 (5·24) years, and 68·5% were men. The mean time (SD) to COVID-19 infection was 5·72 (1·75) years. Based on 17 studies (I2 = 7·34) among 1,481 LT recipients, the cumulative incidence of mortality was 17·4% (95% confidence interval [CI], 15·4–19·6). Mortality was comparable between LT (n = 610) and non-LT (n = 239,704) patients, based on four studies (odds ratio [OR], 0·8 [0·6–1·08]; P = 0·14). Additionally, there was no significant difference in mortality between those infected within one year vs after one year of LT (OR, 1·5 [0·63–3·56]; P = 0·35). The cumulative incidence of graft dysfunction was 2·3% (1·3–4·1). Nearly 23% (20·71–25) of the LT patients developed severe COVID-19 infection. Before infection, 71% and 49% of patients were on tacrolimus and mycophenolate mofetil, respectively. Immunosuppression was modified in 55·9% (38·1–72·2) patients after COVID-19 infection. Interpretation: LT and non-LT patients with COVID-19 have a similar risk of adverse outcomes. Funding: None.